Studi Literatur Pengaruh Perbedaan Budaya dan Agama terhadap Efektivitas Hubungan Konselor-Klien - Yesy Sandry Tumanan; Vemy Alsar; Novrianti Tandiongan Mindi; Ronaldo Stefanus (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This papper reviews a range of studies that examine the influence of cultural and religious differences on the effectiveness of the counselor–client relationship. The main focus is on how cultural identity and religious beliefs shape the way individuals understand problems, interpret personal experiences, and respond to the counseling process. The literature shows that differences in values, communication styles, and spiritual orientations can affect the quality of the relationship, especially during the stages of building trust and setting counseling goals. At the same time, counselors who possess multicultural competence and sensitivity toward religious diversity are better able to adapt their approaches so clients feel respected and emotionally secure. This review also highlights the importance of counselor self-reflection to avoid personal bias in sessions, particularly when working with clients from backgrounds that differ greatly from their own. By examining various academic sources, this article argues that an effective counseling relationship depends not only on technique but also on the counselor’s ability to understand the client’s life context. The findings of this literature review contribute to the development of more inclusive and culturally responsive counseling practices.